Innovative Satellite Monitoring for Information Cadastral Work - Artikov G.A.; Tojidinova F.M. , (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the existing aspects of satellite monitoring for cadastral work and analyzes the issues of monitoring in the cadastre automation system associated with the processing of information on cadastral objects. The main principles of modern GIS technologies in conducting GLONASS/GPS satellite monitoring in the cadastre are listed. The classification of a modern monitoring system based on Monitor3S is given. Innovative programs for conducting satellite monitoring with other countries are considered.